Sistem Kipas Angin Otomatis Dengan Sensor Suhu dan Sensor Ultrasonik Berbasis Arduino - Abyarake Adiyoga; Dian Widiyanto Chandra (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2023)
There are several factors that affect the room temperature, including the weather and the number of people who exceed the capacity. Hot temperature room can interfere our concentration. To overcome this, a tool is needed to decrease the room temperature such as a fan. However, people often forget to turn off the fan, as a result there will be the fan components quickly damage. Based on this case, this research aims to how to make an automatic fan system. By utilizing the DHT11 temperature sensor and ultrasonic sensor HC-SR04 and controlled by Arduino Uno. The result of test is that the fan will automatically turn on when the temperature reaches 300c or the number of people in the room reaches 10 people and the fan will turn off if it does not meet these conditions. With a system like this, it will extend the life of the fan and make it practical to turn on or turn off the fan.